PBL MODEL BASED ON POWER POINT INTERACTIVE MEDIA INCREASING INTEREST IN LEARNING IN CLASS 1 STUDENTS OF FAJAR CITY PRIVATE PRIMARY SCHOOL - Cut Oktanalisa; Siti Mayang Sari; Sariakin; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses qualitative methods whose data sources are obtained through observation, interviews and describing several documentation. One of the components that influences the learning process is that teachers are expected to be able to create interesting learning activities for students so that learning activities can run as expected, achieve learning goals, and get maximum results. Powerpoint media can help an idea become more interesting and clear in its purpose when presented because Powerpoint media will help in creating slides, presentation outlines, electronic presentations, displaying dynamic slides, including interesting clipart, all of which are easily displayed on a computer monitor screen. By using Power Point media, students will be motivated to learn again. Teachers are expected to be able to use the interactive learning media PowerPoint by not only displaying silent reading material with a written focus, but by adding interesting images so that it can increase students' motivation and attention during learning.